GOOD GOVERNANCE PRINCIPLES IN THE FREE NUTRITIONAL MEAL PROGRAM (MBG: CASE STUDY OF STATE SENIOR HIGH SCHOOL 1 PEMALI, PEMALI DISTRICT, BANGKA REGENCY) - Kwartanto Kwartanto; Sena Putra Prabujaya; Yan Megawandi; Darol Arkum (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Free Nutritious Meal Program (MBG) is a public service intervention in education and nutrition that requires sound governance to ensure accurate targeting and long-term sustainability. This study aims to analyze the implementation of Good Governance principles and identify supporting and inhibiting factors in the execution of the MBG Program at SMA Negeri 1 Pemali, Pemali Subdistrict, Bangka Regency. A qualitative approach with a case study design was employed. Data were collected through observations, in-depth interviews with school administrators, the SPPG kitchen team, students, parents, and policy stakeholders, as well as document analysis. The findings reveal that the principles of transparency, accountability, participation, responsiveness, rule of law, effectiveness, and efficiency have been implemented throughout the program, from food preparation to meal distribution and consumption. Nevertheless, administrative standardization remains limited. Supporting factors include clear procedures, effective coordination, prompt responses to technical issues, and cross-sectoral policy support. Inhibiting factors involve inconsistent beneficiary data, weak documentation, limited logistical facilities, unstructured parental participation, and varying student consumption behavior. Strengthening documentation systems, data integration, and structured participation mechanisms is essential to improve governance quality in the MBG Program.